Multiactor Synergy in the Management of Traditional Markets in DKI Jakarta: a Collaborative Governance Study - Anis Baswedan, Rana; Fathurrahman , Reza (International Journal of Social Service and Research, 2025)
The revitalization of traditional markets in DKI Jakarta is part of the local economic modernization efforts outlined in the regional strategic plan. However, the revitalization policy faces challenges in maintaining a balance between physical modernization and preserving the socio-economic functions of traditional markets. This study analyzes the synergy between the DKI Jakarta Provincial Government, the Regional People's Representative Council (DPRD), and Perumda Pasar Jaya in implementing the market revitalization policy using a collaborative governance approach. Through a qualitative study based on secondary data from planning documents, public forums, Pasar Jaya annual reports, and DPRD meeting minutes, this study examines seven collaborative variables that shape institutional synergy. The results indicate that process transparency has increased through the digitization of service systems such as JAKIOS and Pasar Jaya's public reporting. Facilitative leadership is evident in the active role of the DPRD and the Board of Directors in bridging the gap between the government, financial institutions, and traders. Social impacts are reflected in increased trader participation and micro-partnerships with Bank DKI. However, power imbalances persist in strategic policymaking. These findings emphasize the importance of shifting toward collaborative governance that is transparent, deliberative, and socially just.